Enhanced myofibroblast differentiation of eMSCs in intrauterine adhesions - Jun Song; Meiqi Li; Yuan Tao; Yumeng Li; Canrong Mai; Jingting Zhang; Lan Yao; Shaoquan Shi; Jianyong Xu (Stem Cell Research & Therapy)
Abstract Background Intrauterine adhesions (IUA) is one of the most common gynecological diseases and main causes of uterine infertility. Among proposed hypotheses on IUA development, the reduced endometrial regeneration resulting from loss of functional stem cells has been proposed as the key factor affecting the IUA prognosis. However, the underlying mechanisms mostly remain unclear. Because the eMSCs (endometrial mesenchymal stem/stromal cells) play a critical role in both supporting the gland development and also preparing the environment for embryo implantation through decidualization, the characteristics and functions were compared between the eMSCs derived from IUA and non-IUA patients, to uncover the important roles of eMSCs in IUA and also the underlying mechanisms. Methods Endometrium biopsies were collected from IUA patients and controls. The fibrosis features and eMSC distributions were investigated with IHC (immunohistochemistry). Then the eMSCs were isolated and their functions and characteristics were analyzed in vitro. Results Our results indicate that the scar tissues in IUA are characterized with hyper-activation of pro-fibrotic fibroblast and myo-differentiation, along with reduced number of eMSCs. The isolated eMSCs from IUA and controls show similar functions from the perspectives of cell morphology, proliferation, colony formation, exosome secretion, positive ratio of eMSC markers and conventional MSC markers, tri-differentiation efficiency, the ability of suppressing lymphocyte proliferation, cell aging, and promoting vascular tube formation. However, the eMSCs from IUA have reduced levels of decidualization and higher levels of cell migration, invasion, and also myofibroblast differentiation. Further investigations indicate that the TGF-β pathway, which is the major inducer of myofibroblast differentiation, is up-regulated and responsible for the enhanced myofibroblast differentiation potential of eMSCs from IUA. Conclusions In conclusion, we have demonstrated here that the scar tissues in IUA biopsy are characterized with enhanced differentiation of pro-fibrotic fibroblast and myofibroblast. The number of eMSCs is reduced in IUA tissues, and their myofibroblast differentiation capability is increased.